Antitrust's Implementation Blind Side: Challenges to Major Expansion of U.S. Competition Policy. (June 2020) - Jones, Alison; Kovacic, William E.
For several years, a number of commentators have expressed concern that the U.S. has a growing market power problem. Further that dysfunction in the U.S. antitrust institutions, and their failure to protect competition, has damaged the economy. This Article outlines the principal flaws that this commentary attributes to U.S. antitrust policy (the "crisis in antitrust"), and some of the proposals offered to redirect it and restore it as a central tool of economic control. The paper's main purpose is not, however, to debate the condition of competition in the US economy or the merits of the measures proposed. Rather, its objective is to identify the magnitude of the implementation challenges that the proposals for a major expansion of the U.S. antitrust program create and the policy implementation challenges that stand between these soaring reform aspirations and their effective realisation in practice. The paper suggests that even though these "implementation" issues are significant, they have been too quickly overlooked in the commentary. In our view the failure to focus on this important matter risks creating a chasm between elevated policy commitments and the capacity of responsible public to produce expected outcomes. The paper consequently acknowledges and addresses this implementation blindside. It analyses the important impediments that are likely, if not carefully addressed, to hamper delivery of the current proposals and proposes ways to overcome them.